2018
DOI: 10.1007/s00059-018-4706-2
|View full text |Cite
|
Sign up to set email alerts
|

Inherited primary arrhythmia disorders: cardiac channelopathies and sports activity

Abstract: Sudden cardiac death (SCD) in an apparently healthy individual is a tragedy. It is important to identify the cause of death and to prevent SCD in potentially at-risk family members. Inherited primary arrhythmia disorders are associated with exercise-related SCD. Despite the well-known benefits of exercise, exercise restriction has been a historical mainstay of therapy for these conditions. However, since familiarity with inherited arrhythmia conditions has increased and patients are often children and young ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 117 publications
0
6
0
2
Order By: Relevance
“…Si no se dispone de bloqueadores del canal de sodio, y hay sospecha electrocardiográfica de SBr, la realización de un test de esfuerzo (TE) permite evidenciar un pBr I, transitoriamente en el peak del ejercicio 15 , pero de preferencia en los primeros tres minutos de etapa de recuperación, por desbalance autonómico con predominio parasimpático vagal, hallazgo que constituiría un factor independiente de riesgo de FV, principalmente en paciente que se presenta asintomático o con síncope 9,[16][17][18] .…”
Section: Discussionunclassified
“…Si no se dispone de bloqueadores del canal de sodio, y hay sospecha electrocardiográfica de SBr, la realización de un test de esfuerzo (TE) permite evidenciar un pBr I, transitoriamente en el peak del ejercicio 15 , pero de preferencia en los primeros tres minutos de etapa de recuperación, por desbalance autonómico con predominio parasimpático vagal, hallazgo que constituiría un factor independiente de riesgo de FV, principalmente en paciente que se presenta asintomático o con síncope 9,[16][17][18] .…”
Section: Discussionunclassified
“…Officially, 22.8% of all SD cases occurred in individuals between 15 and 45 years of age, and this is a worrisome situation. Preventive measures must be established, especially in high-performance athletes or in those children and young people in whom "innocent" clinical data (dyspnea, palpitations, and/or syncope) are not taken into consideration until it is done retrospectively after the SD of these subjects 19 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Exercise-induced QT prolongation may confer an increased risk in individuals with underlying long QT syndrome (LQTS) because adrenergic surges and emotional stress may trigger arrhythmias in LQT1 and LQT2, respectively. [ 50 53 ] Moreover, exercise-induced prolongation of the QT interval may pose considerable challenges in differentiating physiological adaptation from congenital LQTS, and potentially offering false reassurance to athletes at risk. A recent study demonstrated an exercise-induced QT prolongation phenotype, mimicking congenital LQTS, which reverts back to normal after a period of detraining.…”
Section: Ventricular Arrythmiasmentioning
confidence: 99%